(untitled) (Revista científica Olimpia, 2020)
This descriptive investigation arises with the need to facilitate Physical Culture professionals and health technicians in Angola a proposal for physical exercises necessary for the rehabilitation and care of patients with Arterial Hypertension with an integrative character for health promotion, reduction of factors risk and consequent improvement in health care, early detention and accessible and timely treatment of this pathology. This article aims to develop a concept of physical exercises with an integrative character that, from the prophylactic and therapeutic physical culture, favors the rehabilitation of hypertensive adult patients in the municipal hospital of Namacunde. Because hypertension is a cardiovascular disease that today constitutes a health problem that affects a large portion of the world population, causing complications in different systems of the body leading to death in more serious cases. This study allowed to know the process of care for hypertensive patients from different health centers and hospitals and the impact of physical exercise on the quality of life of these patients; in addition to providing support material to professionals.